Targeted and intelligent nano-drug delivery systems for colorectal cancer treatment - Chai, Meihong; Wang, Shihua; Chen, Yuxin; Pei, Xing; Zhen, Xueyan (Frontiers in Bioengineering and Biotechnology, 2025)
Colorectal cancer (CRC) remains a highly heterogeneous malignancy with significant morbidity and mortality worldwide. Despite advancements in surgery, chemotherapy, immunotherapy, and targeted therapy, treatment efficacy is often hampered by drug resistance and systemic toxicity. In recent years, nano-drug delivery systems (NDDS) have emerged as a promising strategy to enhance therapeutic precision, reduce adverse effects, and overcome resistance in CRC treatment. This review discusses the recent advancements in NDDS for CRC treatment, focusing on the optimization of oral drug delivery systems, the development of tumor-specific targeting strategies, and the design of intelligent delivery systems responsive to the tumor microenvironment (TME). Furthermore, we summarize current challenges in NDDS translation and explore future research directions for enhancing their clinical feasibility and therapeutic impact.